Os poderes das super-heroínas: possibilidade de discussão de conceitos científicos com estudantes do ensino médio - Pinto, Pollyana de Godoy (2020)
This work highlights the process of investigation of science present in the powers of super heroines, by students of public high school in Goiás. Also emphasizing the evolution of the female presence in superhero films, which establishes the encouragement in women in more diverse spaces. The objective of this work was to verify if there was a possibility to relate the fictional powers contained in the characters with formal science. Also, to analyze the scientific level to which these students belonged. The work was carried out in a state college in the metropolitan region of Goiânia with four high school classes, the first two years, a second year and a third year. In total 122 students participated in the work. The students chose eleven super heroines, within the criteria that they themselves defined. They conducted research on the disciplines that best explained their powers, produced written works and oral presentations. The level of approximation between students' previous concepts and scientific concepts in the explanation of powers was evaluated. The results show that the strategy was satisfactory, since 58% of the concepts investigated by the students had a level of approximation with the scientific concept. The data show us that there was involvement and perspective from the students, and that this theme, guarantees motivation allowing a more pleasant science teaching to students.